Asymmetric Dependence Between Stock Market Returns and News During COVID-19 Financial Turmoil (Case Study SSE 50, SET 50, LQ45, and STI Index) - Putri Sulistyowati; Brady Rikumahu (Universitas Muhammadiyah Prof. DR HAMKA., 2021)
The purpose of this study is to see the asymmetric dependence between stock returns and news during the financial turmoil during COVID-19 on the SSE 50, SET 50, LQ45, and STI indices simultaneously or partially. Observations have been carried out for 216 working days from 3 January 2020 to 30 October 2020. The population in this study is the share prices of all stocks listed on the stock exchanges of China, Thailand, Indonesia, and Singapore. The research sample was SSE 50, SET 50, LQ45, and STI indices for the period January 2020 - October 2020. This research is quantitative using quantile regression. Method and involves Eviews 10 in its data analysis. The results show that RavenPack news index (the panic index/PI, the media hype index/HY, the fake news index/FNI, the country sentiment index/CSI, the infodemic index/CTI, dan the media coverage index/MCI), Credit Default Swap (CDS) rate on 5 year bonds issued by the central government, and the daily closing price of gold during weekdays in the period 3 January 2020 - 30 October 2020, there is no significant effect on stock returns on the SSE 50, SET 50, LQ45, and STI indices either simultaneously or partially.